2007
DOI: 10.1007/s10508-007-9234-8
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of HIV/STI Vulnerability and Related Sexual Risk-Taking in a Nationally Representative Sample of Young Croatian Adults

Abstract: Despite the recent increase in the number of HIV infections in Central and Eastern Europe, patterns of sexual behavior have not been extensively researched, particularly among young people. The aim of the present study was to provide a comprehensive assessment of HIV/AIDS-related vulnerability and sexual risk-taking among young adults in Croatia. Data were collected in 2005 using a nationally representative, multi-stage stratified probability sample (n = 1,093) of women and men aged 18-24 years. The focus in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 55 publications
(54 reference statements)
4
21
0
1
Order By: Relevance
“…The first part of the survey was carried out as a face-to-face interview, while the second part, which focused on sexual behaviors and the use of sexually explicit materials, was self-administered to maximize confidentiality. The questionnaire was adapted from an earlier national study of youth sexuality conducted in 2005 (Štulhofer, Graham, Božičević, Kufrin, & Ajduković, 2009). The 2010 questionnaire was tested among 103 high school students and 132 college students in the capital city of Zagreb, Croatia.…”
Section: Questionnairementioning
confidence: 99%
“…The first part of the survey was carried out as a face-to-face interview, while the second part, which focused on sexual behaviors and the use of sexually explicit materials, was self-administered to maximize confidentiality. The questionnaire was adapted from an earlier national study of youth sexuality conducted in 2005 (Štulhofer, Graham, Božičević, Kufrin, & Ajduković, 2009). The 2010 questionnaire was tested among 103 high school students and 132 college students in the capital city of Zagreb, Croatia.…”
Section: Questionnairementioning
confidence: 99%
“…The second part of the questionnaire was self-administered and, among other topics, it covered sexual behaviors, condom use, sexual satisfaction, and pornography use. The original questionnaire was validated in 2005 on a national sample of young adults (Štulhofer, Graham, Božičević, Kufrin, & Ajduković, 2009). In 2010, a revised version was piloted for comprehensiveness and completion time among 103 students from two metropolitan secondary schools and 132 university students.…”
Section: Methodsmentioning
confidence: 99%
“…A multi-sectoral approach that elevates the role of civil society while enhancing the role of legal sector and ultimately decriminalizing IDU harm reduction therapy can provides provisions of care as well as access to legal clinics whereby designing an effective interventions program for IDUs that can remove the "policing" out of public health policy aspects of harm reduction [44,45,32,46,47]. The overall obstacles in providing an effective prevention among IDUs and CSWs is the absence of a multi-sectoral effort and if the war on HIV/AIDS epidemic to be won in the near future in CEE a civil society committed to a universal access to treatment, care and in particular harm reduction programs should be addressed [48][49][50].…”
Section: Prevention Strategies Among Risk Groups and Risk Environmentsmentioning
confidence: 99%
“…Another research study conducted in Croatia examining he HIV/STI vulnerability among the young and adolescent concluded that prevention and intervention efforts are inadequate and capacity building has to be reinforced [49,56]. In Russian Federation and Ukraine the steep rise in the newly registered HIV cases particularly among women has underlined the need for implementing programs of HIV/AIDS prevention that include elements of gender empowerments and encourages the health care delivery systems to introduce measure that are more inclusive and democratic in their nature [51].…”
Section: Healthcare Sectors Role In Prevention Among Young Women Adomentioning
confidence: 99%